Projecting tourism climate suitability in Turkiye under climate change scenarios: insights from the summer simmer index - Adiguzel, Asli Deniz; Zhang, Maomao; Kaya, Asir Yuksel; Karadeniz, Enes; Mantas, Senay (Elsevier Sci Ltd, 2026)
Climate change is one of the most critical global environmental problems that affect tourism by leading to changing temperatures, humidity levels, and increasing the prevalence of extreme weather events. These factors will greatly affect the attractiveness of tourist destinations and the comfort of tourists. More importantly, climate change impacts on tourists' experience and perceptions of tourist destinations. This research used the Summer Simmer Index (SSI) to determine how climate change will affect tourism in seven different geographical regions of Tu & uml;rkiye. Temperature and relative humidity data at monthly averages was collected from CMIP6 projections for 2024, 2050, 2075, and 2100, and for two scenarios SSP1-2.6 and SSP5-8.5 from the Copernicus Climate Data Store and then processed with ArcGIS Pro 3.5.0 software. SSI maps were produced to visualize changes in summer bioclimatic comfort patterns over time. According to the most optimistic climate change scenario for Tu & uml;rkiye, average summer temperatures are projected to rise by 2.35 degrees C by 2050 and 4 degrees C by 2100. In this case, bioclimatic comfort zones are expected to cover 31.14% of the country's land area by 2100. Under the most pessimistic climate change scenario, average summer temperatures are projected to rise by 7.79 degrees C by 2100, while bioclimatic comfort zones are projected to constitute 18.59% of the country's land area. The findings indicated that under the most pessimistic scenario, the Mediterranean and Aegean Regions of Tu & uml;rkiye will experience the larges decline in thermal comfort; therefore, negatively impacting the sustainability of coastal tourism. However, based on their relatively moderate climates, regions such as the Black Sea, the Eastern Anatolia, and the Central Anatolia Regions may become more suitable destinations for summer tourism. The findings support the need for an evaluation of the seasonality of tourism, evaluation of visitor preferences, and development of tourism infrastructure based on anticipated climate change conditions. The results also demonstrate that SSI is a valuable tool for guiding adaptive tourism strategies under changing climate scenarios. (c) 2026 COSPAR. Published by Elsevier B.V. All rights are reserved, including those for text and data mining, AI training, and similar technologies.
Keywords: Climate change; Tourism; Climate scenarios; Bioclimatic comfort; Summer Simmer Index; Turkiye